The role of GABA in the regulation of GnRH neurons - Watanabe, Miho; Fukuda, Atsuo; Nabekura, Junichi (Frontiers in Neuroscience, 2014)
Gonadotropin-releasing hormone (GnRH) neurons form the final common pathway for the central regulation of reproduction. Gamma-amino butyric acid (GABA) has long been implicated as one of the major players in the regulation of GnRH neurons. Although GABA is typically an inhibitory neurotransmitter in the mature adult central nervous system, most mature GnRH neurons show the unusual characteristic of being excited by GABA. While many reports have provided much insight into the contribution of GABA to the activity of GnRH neurons, the precise physiological role of the excitatory action of GABA on GnRH neurons remains elusive. This brief review presents the current knowledge of the role of GABA signaling in GnRH neuronal activity. We also discuss the modulation of GABA signaling by neurotransmitters and neuromodulators and the functional consequence of GABAergic inputs to GnRH neurons in both the physiology and pathology of reproduction.